Carbon isotope perturbations are not primarily driven by volcanism during the Late Paleozoic Ice Age - Luojing Wang; Dawei Lv; Zhihui Zhang; Stephen E. Grasby; John L. Isbell; Jun Shen; Jianghai Yang (Communications Earth & Environment)
Abstract The late Paleozoic ice age (LPIA) was the longest-lived glaciation of the Phanerozoic, and its demise marks Earth’s only recorded transition from an icehouse to a greenhouse state since the occurrence of vascular plants and complex terrestrial ecosystem. While global volcanism has been widely considered a key driver of carbon cycle during this period, limited high-resolution records have constrained our understanding. Here, we use high-resolution carbon isotope and mercury records from the North China Craton, spanning the late Gzhelian to early Kungurian stages, to evaluate the relationship between carbon cycle perturbation and volcanism. We identify two negative carbon isotope excursions during the late Gzhelian and early Asselian, both coinciding with climate warming. Our data reveal a variable relationship between carbon cycle disturbances and mercury records, suggesting volcanism was not the only trigger. Instead, they may result from the superimposition of multiple mechanisms, including tundra conditions, methane release, or orbitally-paced climate changes.